Effect of Vitamin D3 and Calcium Carbonate Supplementation on Muscle Strength in Postmenopausal Women Living with HIV. Issue 8 (November 2020) - Yin, Michael T; Bucovsky, Mariana; Williams, John; Brunjes, Danielle; RoyChoudhury, Arindam; Colon, Ivelisse; Ferris, David C; Olender, Susan; Schulze, P Christian; Sharma, Anjali; Zeana, Cosmina; Zingman, Barry; et al.
Background: Both falls and fractures are increased in older persons living with HIV (PLWH). Low serum total 25-hydroxyvitamin D (25-OHD) levels have been associated with falls, fractures and poor muscle strength. We hypothesized that vitamin D (VitD) supplementation would improve muscle strength in postmenopausal PLWH. Methods: In a 12-month prospective, randomized, double-blind, study of 69 African American and Hispanic post-menopausal PLWH on antiretroviral therapy with 25-OHD ≥10 ng/ml and ≤32 ng/ml, we investigated the effects of daily low (1, 000 IU; n =31) and moderate (3, 000 IU; n =38) cholecalciferol doses on lean mass and strength. Change in lean body mass was assessed by dual-energy X-ray absorptiometry (DXA), and isometric and isokinetic muscle strength in the dominant lower extremity was assessed using the Biodex System 4 Pro. Results: Mean age was 56 ±5 years, median CD4 + T-cell count 722 cells/mm 3 and 74% had HIV RNA≤50 copies/ ml. Serum 25-OHD did not differ at baseline, but was higher in the moderate than low VitD group at 6 and 12 months. In both groups, there were significant increases in lower extremity isokinetic torque, work and power at 12 months, with no change in lean mass. Conclusions: VitD supplementation was associated with a modest increase in lower extremity strength in postmenopausal PLWH, without a concomitant increase in muscle mass. Magnitude of increase in strength were similar with 3, 000 IU and 1, 000 IU daily. Future larger studies will be required to determine the optimal dose of VitD to improve muscle strength and to determine whether supplementation reduces the risk of falls and fractures in PLWH.